Is this guy for real? : the unbelievable Andy Kaufman - Brown, Box (First Second, an imprint of Roaring Brook Press, 2018)
Comedian and performer Andy Kaufman's resume was impressive- a popular role on the beloved sitcom Taxi, a high-profile stand-up career, and a surprisingly successful stint in professional wrestling. Although he was by all accounts a sensitive and thoughtful person, he's ironically best remembered for his various contemptible personas, which were so committed and so convincing that all but his closest family and friends were completely taken in. Why would someone so gentle-natured and sensitive build an entire career seeking the hatred of his audience? What drives a performer to solicit that reaction?